O Novo Ensino Médio – Lei nº 13.415/2017: contributo para a contrarreforma do estado brasileiro - Sabino, Thiago Chaves (2023)
In 2016, Brazil was marked by an illegitimate impeachment process that removed former President Dilma Roussef (PT), in order to advance measures in favor of state deregulation and withdrawal of working class rights. As a result of this context, there were profound changes characterized by setbacks in the State and in Brazilian education. In the scope of basic education, the New High School (NEM), instituted by Law nº 13.415/2017 (Brasil, 2017), was approved in an undemocratic way along with several other measures that changed laws and the Federal Constitution of 1988. This scenario requires analysis and follow-up in perspective, seeking to identify the direction in which the new pedagogical, economic and ideological determinations of the current project point. The general objective of this study concentrates its efforts on investigating the constitutive movements of the NEM implementation project in order to understand the phenomenon in its entirety and its place in the application of counter-reforms in the Brazilian State. For a more precise definition, we will use the category of counter-reform, based on the concept of Behring (2008). In order to research the object in its movement, we resorted to the use of the method of historical and dialectical materialism, to unveil the fetishized world of appearance, relating the essence and the phenomenon, understanding them as part of the same reality, since the phenomenon hides the essence. The adopted method allows understanding the relationship between the singularities of the NEM and the particularities of the counter-reform process of the Brazilian State, in the context of contemporary world capitalism. We also rely on the category of imperialism, understanding it as a superior phase of capitalism, from Lenin (2002), and the domain of financial capital and monopolies and oligopolies. By understanding and studying the counter-reform of Brazilian high school in the context of the application of counter-reforms in Brazil, especially since the 1990s, taking into account the institutional rupture of the legal-parliamentary coup of 2016, we conclude that it has an intrinsic relationship with the counter-reform of the Brazilian State, imbricating a new fragmented pedagogical-curricular proposal to the flexible and precarious labor market, increasingly without labor and social security rights, and to an ideology for the workers that shields them from class consciousness, trying to effect a bond with the employer class and entrepreneurship. The NEM, therefore, represents a strong pillar of support for the counter- reform of the State and contemporary Brazilian capitalism.